Identification of qPCR reference genes suitable for normalising gene expression in the developing mouse embryo [version 1; peer review: 1 approved, 2 approved with reservations] - John C.W. Hildyard; Richard J. Piercy; Dominic J. Wells (Wellcome Open Research, 2021)
Background: Progression through mammalian embryogenesis involves many interacting cell types and multiple differentiating cell lineages. Quantitative polymerase chain reaction (qPCR) analysis of gene expression in the developing embryo is a valuable tool for deciphering these processes, but normalisation to stably-expressed reference genes is essential for such analyses. Gene expression patterns change globally and dramatically as embryonic development proceeds, rendering identification of consistently appropriate reference genes challenging. Methods: We have investigated expression stability in mouse embryos from mid to late gestation (E11.5–E18.5), both at the whole-embryo level, and within the head and forelimb specifically, using 15 candidate reference genes (ACTB, 18S, SDHA, GAPDH, HTATSF1, CDC40, RPL13A, CSNK2A2, AP3D1, HPRT1, CYC1, EIF4A, UBC, B2M and PAK1IP1), and four complementary algorithms (geNorm, Normfinder, Bestkeeper and deltaCt). Results: Unexpectedly, all methods suggest that many genes within our candidate panel are acceptable references, though AP3D1, RPL13A and PAK1IP1 are the strongest performing genes overall. HPRT1 and B2M are conversely poor choices, and show strong developmental regulation. We further show that normalisation using our three highest-scoring references can reveal subtle patterns of developmental expression even in genes ostensibly ranked as acceptably stable (CDC40, HTATSF1). Conclusion: AP3D1, RPL13A and PAK1IP1 represent universally suitable reference genes for expression studies in the E11.5-E18.5 mouse embryo.